Early childhood lower-airway symptoms and airway hyperresponsiveness linked to school-age small-airway dysfunction - Anette M. Määttä, MD; L. Pekka Malmberg, MD, PhD; Anna S. Pelkonen, MD, PhD; Mika J. Mäkelä, MD, PhD (Journal of Allergy and Clinical Immunology: Global)
Background: The role of early airway hyperresponsiveness (AHR) in the subsequent small-airway lung function remains unclear. Objective: We assessed via a prospective follow-up study the small-airway lung function of schoolchildren with early childhood lower-airway symptoms and AHR to methacholine and compared the findings to the measurements of reference children with no previous or current lung diseases. Methods: During 2004-11, we measured atopic markers, lung function, and airway responsiveness to methacholine in 193 symptomatic children <3 years old. In 2016-18, a follow-up sample of 84 schoolchildren and 40 reference children were assessed for atopic parameters, spirometry, and small-airway lung function. Analysis was performed on the basis of early childhood AHR, early childhood atopy (defined as a positive skin prick test result), and exposure to parental smoking reported in a questionnaire. All the results were compared with those of the reference group. Results: Schoolchildren with early childhood lower-airway symptoms and AHR had higher prebronchodilator area under the reactance curve (AX) z score, lower forced expiratory flow at 50% of forced vital capacity (FEF50%) z score, and higher lung clearance index (LCI) 2.5% compared with those without early childhood AHR and reference children. Moreover, AX and FEF50% z scores only partly improved after bronchodilation. Early childhood atopy and exposure to parental smoking were not associated with school-age small-airway dysfunction. Conclusion: AHR in symptomatic young children associated with subsequent persistent small-airway dysfunction. Further studies with larger samples of symptomatic young children are warranted to determine whether this connection predicts the development of asthma or other obstructive pulmonary diseases as the children grow.